Pavement condition survey in road along Kampung Selancar Pagoh - Salim, Salman; Mazlan, Amir Osman; Muhammad Jalil, Amy Ashmiera; Mohamed Azmi, Muhammad Afiq Firdaus; Hassan, Nurul Hafizah; Md Yaacob, Nur Emylia Absarina (Penerbit UTHM, 2020)
Road maintenance involves in remedying defects such as potholes, patch, edge defects and etc. that occurs in the carriageway. The corrective maintenance and providing treatments is carried out from time to time to slow the rate of deterioration (preventative maintenance). Road maintenance is essential to preserve the road in its originally constructed condition, protect adjacent resources and user safety and provide, and convenient travel along the route. Before doing any road maintenance, the defects should be determined first. The place chosen in Kampung Selancar, Pagoh which is the defects determination are carried out along 1km carriageway...